The anomalous optical conductivity in hole-doped cuprate superconductors. (February 2018) - Gao, He; Yuan, Feng; Chen, Shaou; Zhao, Huaisong
Abstract: Based on the renormalized t - J model and self-consistent mean field theory, the doping and energy dependence of optical conductivity and effective electron number in cuprate superconductors are discussed. As the result of the presence of the pseudogap in normal state, the optical conductivity exhibits two main components from underdoping to overdoping, a narrow band peaked around zero energy and a broadband centered in the mid-infrared region which deviates the Drude formula. With increasing the doping concentration, the spectral weight of the optical conductivity suppressed strongly in underdoped region increases quickly, and the peak position of the mid-infrared band moves towards to the lower energy region, then incorporates into the narrow band centered in zero energy in the heavily overdoped region. By virtue of the integral, the effective electron number is obtained, and it increases monotonically from zero energy to mid-infrared characteristic energy with increasing energy, then shows a plateau feature when the energy is larger. In particular, the mid-infrared characteristic energy scales with the pseudogap, reflecting the presence of the mid-infrared band is the result of the pseudogap effect. Highlights: The pseudogap determines the non-Drude type of optical conductivity of cuprates. The effective electron number shows a plateau feature over the mid-infrared energy. The characteristic peak position of mid-infrared band scales with effective pseudogap.